Republicanism and liberalism: a possible consensus around an idea of civic virtue - Santos, Edson kretle (2022)
Currently, republicanism is accused of thinking of civic virtue as linked to an ideal of the good life and, therefore, impossible to be realized in modern, plural and neutral societies. On the other hand, liberalism is accused of basing its argument on the ideal of individual autonomy, leading to political fragmentation. Faced with this clash, we intend to present the republican civic virtue as one of the political virtues required by political liberalism. The adequate foundation of this hypothesis will allow us to make sense of the recent proposals of a liberal republicanism as an answer to some of the current problems of liberal democracies.